Parechovirus A in Hospitalized Children With Respiratory Tract Infections: A 10-Year-Long Study From Norway. (26th April 2021) - Skanke, Lars Høsøien; Lysvand, Hilde; Heimdal, Inger; Moe, Nina; Krokstad, Sidsel; Christensen, Andreas; Risnes, Kari; Nordbø, Svein Arne; Døllner, Henrik
Abstract : During a 10-year-long period, Parechovirus A occurred at similar rates in hospitalized children with respiratory tract infections (RTI) and hospital controls. In both groups, viral codetections were common. Parechovirus A has a limited role in hospitalized children with RTI. Abstract: Background: The role of Parechovirus A (PeV-A) in hospitalized children with respiratory tract infections (RTIs) is unclear. We studied the occurrence and impact of PeV-A over 10 years. Methods: Children from Sør-Trøndelag County, Norway, hospitalized with RTI and a comparison group of asymptomatic children admitted to elective surgery, were prospectively enrolled from 2006 to 2016. Nasopharyngeal aspirates were cultured and analyzed with polymerase chain reaction tests for PeV-A and 19 other pathogens. The cycle threshold levels of PeV-A were reported as measures of viral genomic loads. Parechovirus A-positive samples were genotyped by amplification and sequencing of the VP3/VP1 junction. Results: Parechovirus A was detected in 8.8% (323/3689) patients with RTI and in 10.1% (45/444) of the children in the comparison group ( P = .34). Parechovirus A genotyping (n = 188) revealed PeV-A1 (n = 121), PeV-A3 (n = 15), PeV-A5 (n = 6), and PeV-A6 (n = 46). Viral codetections occurred in 95% of patients and in 84% of the children in the comparison group ( P = .016). In multivariable logistic regression analysis, RTI was unrelated to PeV-A genomic loads, adjusted for other viruses and covariates. Similar results were found for PeV-A1 and PeV-A6. Conclusions: Parechovirus A and viral codetections were common in hospitalized children with RTI and asymptomatic children in a comparison group. Our findings suggest that PeV-A has a limited role in hospitalized children with RTI.